Frailea erythracantha (Cactaceae): a new species from Pampa Grasslands, Rio Grande do Sul State, Brazil - Pontes, Rodrigo Corrêa; Deble, Anabela Silveira De Oliveira; Deble, Leonardo Paz (Phytotaxa, 2018)
The South American genus Frailea includes taxa which are no sufficiently known from the taxonomical point of view. Based on field surveys, nomenclatural types and other specimens and review of literature we found an interesting population of a Frailea species from western region of the State of Rio Grande do Sul, Brazil which was described as Frailea erythracantha sp. nov. Data regarding its geographic distribution, phenology, habitat, conservation, and morphological affinities with related species are provided.